2016
DOI: 10.1093/mnras/stw1117
|View full text |Cite
|
Sign up to set email alerts
|

Models of the thermal evolution of the intergalactic medium after reionization

Abstract: Recent years have brought more precise temperature measurements of the low-density intergalactic medium (IGM). These new measurements constrain the processes that heated the IGM, such as the reionization of H I and of He II. We present a semi-analytical model for the thermal history of the IGM that follows the photoheating history of primordial gas. Our model adopts a multi-zone approach that, compared to previous models, more accurately captures the inhomogeneous heating and cooling of the IGM during patchy r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 75 publications
6
115
1
Order By: Relevance
“…However, there is generally a lack of consistency between these measurements and those from other studies (Ricotti et al 2000;McDonald et al 2001;Zaldarriaga et al 2001;Lidz et al 2010). In particular Lidz et al (2010) found evidence for a much hotter IGM at z 3.5 than expected from current models (Puchwein et al 2015;Upton Sanderbeck et al 2016;Oñorbe et al 2016), in disagreement with Becker et al (2011).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…However, there is generally a lack of consistency between these measurements and those from other studies (Ricotti et al 2000;McDonald et al 2001;Zaldarriaga et al 2001;Lidz et al 2010). In particular Lidz et al (2010) found evidence for a much hotter IGM at z 3.5 than expected from current models (Puchwein et al 2015;Upton Sanderbeck et al 2016;Oñorbe et al 2016), in disagreement with Becker et al (2011).…”
mentioning
confidence: 75%
“…Irrespective of the nature of these sources, if they reionized intergalactic helium at z 4, these sources also likely contributed substantially to H I reionization (Madau & Haardt 2015). Unfortunately, it is not currently possible to probe the ionization state of He II via far-UV He II Lyα absorption at z 4, and constraints on He II reionization from the thermal state of the IGM do not all agree (Lidz et al 2010;Becker et al 2011;Upton Sanderbeck et al 2016). This paper introduces a new method to constrain the timing of He II reionization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equally poorly understood is the thermal history of the IGM, which reflects the timing and duration of reionization as well as the nature of ionizing sources. Measurements of the IGM temperature evolution from redshift 2 to 5 are not consistent with the monotonic increase with redshift expected after the completion of hydrogen reionization, and require a substantial injection of additional energy, likely from the photoionization of He II (Becker et al 2011;Upton Sanderbeck et al 2015). …”
Section: Introductionmentioning
confidence: 87%
“…The interplay of these two factors determines the temperature of these regions of average density. The average temperature of these regions show two characteristic bumps as a function of redshift: one initial increase from T ∼ 200 K to T ∼ 10 4 K as a result of hydrogen reionization at 8 z 10, and a subsequent increase in temperature from T ∼ 10 4 K to T ∼ 2 × 10 4 K at 2 z 3.5 as a result of helium reionization (Furlanetto & Oh 2008;Puchwein et al 2015;Upton Sanderbeck et al 2016). In between the two epochs of reionization, and following helium ii reionization, adiabatic cooling dominates, and so the average temperature decreases.…”
Section: Temperature At Mean Densitymentioning
confidence: 99%